Prosedur Pembuatan Nomor Induk Berusaha (NIB) Di Kelurahan Klampok Kota Blitar - Maghfirotika, Azaaima; Kusumasari, Indah Respati (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This paper discusses the procedure for making a Business Identification Number (NIB) in Klampok Village, Sananwetan District, Blitar City. This paper will discuss in detail how to create an NIB account so that business actors can have a legal permit to establish their business. From what we already know, that Indonesia is a country that has a lot of MSMEs scattered. Indonesia is a country that has a variety of diversity, ranging from abundant natural wealth to various cultures. By utilising the existing wealth, the Indonesian people come up with new innovations to sustain their lives by producing materials that are in the surrounding environment to be developed for the better. So it is not surprising that this country has various types of businesses that vary in each region. With the existence of various types of businesses, making this country many job opportunities. This can make Indonesia's economic growth increase. With that, the government made innovations to facilitate every business actor by reforming the business licensing system through the Business Identification Number (NIB). The NIB can be accessed through the Risk-Based OSS system (OSS RBA) which has been coordinated by the Indonesian government with Investment (BKPM). NIB itself is an official identity number distributed by the government to every business operating in Indonesia, including MSMEs. Therefore, it is important, especially for small and medium enterprises (MSMEs), to apply for a business licence to help and facilitate the sustainability of their business. Through the NIB registration post, MSMEs will get a detailed explanation of the requirements and procedures for NIB registration. This helps reduce confusion and difficulties that may be faced by MSMEs in taking care of NIB registration.